(3JGQjN HdGO GdTGe GdGbJUGOj aj GdYUQ GdCehj (B/s - (3QMGd, YGWas ((3HjQhJ(B: s (3HjSGf ddfTQ hGdJhRjY(B, s, 2000)
(3GdCMhGd GdGbJUGOjI aj GdTGe bHd GdYUQ GdCehj;GdCMhGd GdRQGYjI aj GdYUQ GdCehj,GdCMhGd GdJLGQjI,GdCMhGd GdUfGYjI,GdfXe GdeGdjIs
(3HHdjhZQGajG(B:(3U(B.333-350s
Keywords: (3GdJGQjN GdGbJUGOjs; (3GdTGes